Chronicity of Uncorrected Hyponatremia and Clinical Outcomes in Older Patients Undergoing Hip Fracture Repair - Ayus, Juan Carlos; Fuentes, Nora; Go, Alan S.; Achinger, Steven G.; Moritz, Michael L.; Nigwekar, Sagar U.; Waikar, Sushrut S.; Negri, Armando Luis (Frontiers in Medicine, 2020)
Background: Chronic hyponatremia is a risk factor for hip fracture but remains uncorrected in most patients. This study evaluated if preoperative chronicity of uncorrected hyponatremia influences outcomes after hip fracture repair. Materials and Methods: Evaluated were older patients hospitalized for hip fracture repair between 2007 and 2012 with plasma sodium measured at admission and ≥1 preadmission outpatient measurement. Patients were classified as being normonatremic (NN; plasma sodium 135–145 mmol/L), chronic prolonged hyponatremia (CPH; ≥2 consecutive plasma sodium values <135 mmol/L over >90 days), or recent hyponatremia (one plasma sodium <135 mmol/L within 30 days before admission with previously normal plasma sodium). Length of hospital stay, in-hospital death, post-operative complications, 30-day readmission, and long-term mortality were the evaluated outcomes. Multivariable Cox regression was used to evaluate the association of hyponatremia status with outcomes. Results: Among 1,571 eligible patients, 76.7% were NN, 14% had CPH, and 9.1% had RH. Compared with NN patients, CHN patients were older and had more prior heart failure, alcoholism, and anticonvulsant drug use. In multivariable analyses, neither CPH or RH was associated with hospital length of stay, in-hospital or 30-day death, or 30-day readmission, while RH was associated with post-operative sepsis [adjusted odds ratio (aOR) 1.84, 95% CI: 1.01–3.35). Only CPH was independently associated with long-term all-cause death (OR 1.53, 95% CI: 1.12–2.09). Conclusions: Hyponatremia affects nearly 25% of patients undergoing hip fracture repair. Preoperative chronic untreated hyponatremia is associated with increased post-operative mortality following surgical repair of a hip fracture in older patients. Future studies should evaluate if correction of hyponatremia could decrease long-term mortality after hip fracture repair.